Quality of selected groundwater sources in Barangay Kirayan Sur, Miagao, Iloilo - Sy, Maricris R.
The study was conducted to assess the physico-chemical and microbiological quality of groundwater sources in Barangay Kirayan Sur, Miagao, Iloilo.